Digital Planning for Mini-Implant Supported Palatal Expander in Open-Bite Treatment - C, Szuhanek; M, Babat; A, Popa (Journal of Dentistry And Oral Implants, 2020)
Open bite malocclusion, due to it’s multifactorial etiology, has always been considered a difficult problem to treat. Often associated with transverse maxillary deficiency, this is a real challenge in the field of orthodontics. The traditional approach, for this type of anomaly, in adult patients, is orthognathic surgery and RME (rapid maxillary expansion). There are several approaches to the treatment of adult patients using digital technology. Mini-implant supported palatal expander limits the side effects of the conventional RME and is less invasive compared to orthognathic surgery. Precise and predictable mini-implant insertion, using a customized surgical guide, provides a safe therapeutic approach. This case report combines Cone-beam computed tomography (CBCT), laser scan superimposition, computer-aided design (CAD) and 3D printing in order to design and print a customized surgical guide for orthodontic mini-implant insertion. A CBCT scan was performed to determine the optimal site for mini-implants’ placement. Using the 3Shape Trios Intraoral Scanner the maxilla and the mandible were laser-scanned. Blue Sky Plan 4 software was used to design the surgical guide, and RayWare software was used for printing it. 4 mini-implants were inserted using a safe and predictable technique. The 3D technology represents the future of orthodontics, reducing the risks, chair-side time while providing the best treatment plan for the patient.
Keywords: Mini-Implant; Palatal Expander; Open-Bite Malocclusion; Digital Planning; Cone-Beam Computed Tomography (CBCT); Surgical Guide